Этнос и индивид как субъекты социальной реальности: закономерности взаимосвязи и их современное состояние - Емельянова, Юлия Павловна; Ємельянова, Юлія Павлівна; Yemelianova, Yuliia P. (Східноєвропейський національний університет імені Лесі Українки, 2015)
С позиции глобального эволюционного подхода проанализированы основные закономерности формирования и исторического сосуществования двух субъектов социального мира – этнического сообщества (этноса) и этнофора (индивида). Генерализация роли культуры в процессе эволюционного становления и усложнения социального мира позволяет показать взаимную обусловленность формирования этноса как коллективного субъекта и индивида (субъекта индивидного). В таком контексте тенденция «атомизации», «капсулизации» современного индивида может рассматриваться как проявление эволюционной необходимости формирования более сложного субъекта социального мира. Ethnic community (Ethnos) and ethnophor (Indivual) are two subjects of social universe that are analysed in this article from the evolution approach point of view. Generalisation of the role of culture in the process of evolutionary becoming and complication of the human world is a methodological base for this analysis. Ethnos as a collective subject is examined as a functional organisation created by individuals, as a psycho-cultural construction that does not have objectivity. The author substantiates that ethnos and individual are interdependent in the evolutionary process, besides, the process of becoming of ethnos as a collective subject of social reality contains preconditions for becoming of subjectivity of an indi-vidual. Potential subjectivity of social material assumes not only emerge of subjects and their competition, but movement of social material towards increasingly complex form of subjectivity. In such context «atomization», «crystallization», of an individual which is an ongoing object of analysis by social theory, can be seen as a demonstration of evolutionary tendency in forming an individual as of a more complex subject of social universe.
Ethnos and Individual as Subjects of Social Reality: Consistent Patterns of Interconnection in its Modern State.
Keywords: глобальный эволюционный процесс; антропосоциокультурогенез; субъект социальный; духовная сфера жизни человека; «атомизация» индивида; украинский этнос; Global evolutionary process; anthropological social cultural genesis; social subject; spiritual sphere of human existence; «atomisation» of an individual; Ukrainian ethnos